Pembelajaran Keterampilan Berbicara dengan Menerapkan Metode Curah Gagasan (Brainstorming) - Syamhari Syamhari (Jurnal Adabiyah: Humanities and Islamic Studies, 2012)
Speaking skill is one of four language skills include listening, reading, and writing. Speaking is very important for the existence of socio and culture. Brainstorming method is one method that is used to arrange idea by revealing many ideas from the topic given. It is also used both before speaking or at the time of speaking. Brainstorming method can be done in group or individual. If it is in group, someone has to become a minute notes and has to write down the ideas revealed. On this case, students do not need to worry about the grammar, spelling, and so forth, even about the truth of members’ explanation. The implementation of brainstorming method in improving speaking skill has main advantage through process. The learning process by implementing brainstorming method can support students to think actively, to reveals idea, and stimulate students to express their ideas.